2017
DOI: 10.1002/pssb.201600699
|View full text |Cite
|
Sign up to set email alerts
|

100‐nm thick single‐phase wurtzite BAlN films with boron contents over 10%

Abstract: Growing thicker BAlN films while maintaining single‐phase wurtzite structure and boron content over 10% has been challenging. In this study, we report on the growth of 100 nm‐thick single‐phase wurtzite BAlN films with boron contents up to 14.4% by MOCVD. Flow‐modulated epitaxy was employed to increase diffusion length of group‐III atoms and reduce parasitic reactions between the metalorganics and NH3. A large growth efficiency of ∼2000 μm mol−1 was achieved as a result. Small B/III ratios up to 17% in conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 19 publications
1
41
1
Order By: Relevance
“…Furthermore, these needles do not form a completely coalesced layer, which is also obvious in the plan view image. The column diameter varies from 20 to 40 nm, which is in good agreement with grain sizes for B‐III‐N observed in literature …”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, these needles do not form a completely coalesced layer, which is also obvious in the plan view image. The column diameter varies from 20 to 40 nm, which is in good agreement with grain sizes for B‐III‐N observed in literature …”
Section: Resultssupporting
confidence: 90%
“…Recent studies have shown that B‐III‐N based crystals can exhibit lattice twinning or tilting . SAED measurements (Figure a–d) were carried out to prove the absence of lattice twinning and polycrystalline growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations